Quasi-Static Indentation Properties of Aluminium Foam-Frp Sandwich Panel - Raihanah Hashim, Ummu; Jumahat, Aidah; Fashan Md Ghazali, Muhammad (International Journal of Engineering and Technology, 2018)
Synthetic FRP have been used for many years in wide applications owing to their versatility and good performance. However, environmental problems caused by extensive use of polymeric materials arise mainly due to lack of landfill spaces and depletion of finite resources of fossil raw materials, such as petroleum or natural gas. Hence, materials derived from natural products are emerging as potential substitutes for petroleum-based material. The usage of natural fibre reinforced polymer (NFRP) composite have triggered considerable interest to explore the usefulness of this material. Excellent energy absorption of sandwich-structured composite made it a versatile structure used in various industries such transportation, automotive, building construction and marine. On top of that, the research data on aluminium foam as a core material in sandwich panel are limited and need to be further studied. This research is aimed to determine the quasi-static indentation properties of Basalt Fibre Reinforced Polymer/Aluminium Foam (BF-AF) sandwich panel and compare with the properties of Glass Fibre Reinforced Polymer/Aluminium Foam (GF-AF) sandwich panel. In this study, BFRP and GFRP composites with nanosilica were fabricated using vacuum bagging method. Aluminium foam was used as a core in the sandwich panel structure. The quasi-static indentation tests were performed using 10mm indenter and the specimen size was 50mm x 50mm with thickness of 3mm. The effect of aluminum foam on indentation properties were studied. The results showed that the addition of nanosilica enhanced the energy absorption, depth of penetration and damage area of the composites. The indentation properties of BF-AF were higher than those of GF-AF sandwich panel composites. Therefore, this research contributes to a new knowledge on the properties of aluminium foam-FRP composite materials